2015
DOI: 10.1038/aps.2015.26
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nav1.7 channels by methyl eugenol as a mechanism underlying its antinociceptive and anesthetic actions

Abstract: Methyl eugenol is a potential candidate as an effective local anesthetic and analgesic. The antinociceptive and anesthetic effects of methyl eugenol result from the inhibitory action of methyl eugenol on peripheral Na(+) channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 41 publications
0
36
1
Order By: Relevance
“…However, the underlying mechanisms of these functions are still actively being investigated. A previous study reported that ME inhibited the voltage-gated sodium Na V 1.7 channels, which underlies its antinociceptive and anesthetic actions (Wang et al, 2015). Additionally, ME is an agonist of the TRPA1 channel (Moon et al, 2015); blockade or genetic ablation of the TRPA1 channel decreases anxietylike behaviors in mice (de Moura et al, 2014;Lee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the underlying mechanisms of these functions are still actively being investigated. A previous study reported that ME inhibited the voltage-gated sodium Na V 1.7 channels, which underlies its antinociceptive and anesthetic actions (Wang et al, 2015). Additionally, ME is an agonist of the TRPA1 channel (Moon et al, 2015); blockade or genetic ablation of the TRPA1 channel decreases anxietylike behaviors in mice (de Moura et al, 2014;Lee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ME was recently reported to counteract anorexigenic signals for feeding regulation in association with GABAergic phasic inhibition in the CeA (Zhu et al, 2018). Other potential cellular targets for ME within the CNS include voltage-gated sodium channels (Wang et al, 2015) and transient receptor potential ankyrin 1 (TRPA1) channels (Moon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, although TRPV1 and TRPV3 channels share significant homology, TRPV3 channels do not respond to capsaicin or acidic pH [17]. Cutaneous TRPM8 channels are the principle receptors involved in environmental cold sensation and cold pain transduction [13, 19]. …”
Section: Transient Receptor Potential Cation Channel (Trp) Physiologymentioning
confidence: 99%
“…Significantly, no side effects were observed in these test animals [70]. Another study found that methyl eugenol, an herbal extract, inhibited Nav 1.7 preferentially in both the inactivated and open states [19]. This compound has not been evaluated in animal or human studies as it pertains to induction of analgesia [19].…”
Section: Voltage-gated Sodium Channel Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation